Should we be afraid of lactate? Beneficial effects of elevated blood lactate concentration on high-intensity exercise performance - Hofmann, P.; Sieder, M.; Müller, A.; Tschakert, G. (Science and Skiing VII, 2018)
It has long been suggested that lactate (La) is a waste product, and many people still believe this myth despite the fact that La metabolism has been described in detail for decades (Brooks, 2009). Lactate was shown to be an energy source, a gluconeogenetic precursor and a regulator, and the La shuttle theory describes the delicate balance of muscular La production and La oxidation during exercise (Brooks 1986a, 2007). A three-phase response results in a balanced La production and oxidation at muscular level at low intensities (no increase of La in blood), a systemic whole-body balanced level at moderate intensities (La in blood is elevated but stable after a first increase), or no balance where La production exceeds the oxidation capacity, leading to a continuous increase of La and acidosis, and finally termination of exercise due to exhaustion (Hofmann & Tschakert, 2010). This phenomenon of shuttling La has been described in detail for exercising muscles (Brooks, 2009), but also for other organs and tissues. It is therefore of substantial interest to investigate this general shuttle mechanism in more detail. An interesting practical application of the La shuttle theory is the elevation of La by high-intensity pre-load (such as intense warm-up) ahead of an anaerobic workout. This review focuses on applying the shuttle theory to high-intensity anaerobic exercise and describes the paradox effects of a high pre-load La elevation on subsequent anaerobic exercise of non-preloaded muscles.